Pengabdian Masyarakat International Pendampingan dan Pembuatan Alat Bantu Gerak (Orthosis) Bersama SRC Holland - Sudadi Pranata; Chandra Lukita; Amroni Amroni; Ridho Taufiq Subagio; Kusnadi Kusnadi; Lena Magdalena; Suwandi Suwandi; Chairun Nas (Pusat Riset dan Inovasi Nasional, 2021)
This International Community Service activity is motivated by the community's need for quality assistance and mobility aids (orthoses). People who have physical limitations often face challenges in getting access to mobility aids that meet international health needs and standards. This assistance covers various aspects, including providing emotional support, education and training regarding the use of mobility aids. The focus of International PkM activities aims to increase the independence and quality of life of individuals with physical limitations. The method of International PkM activities consists of socialization, patient registration and examination, making orthosis devices, installing equipment, monitoring and evaluating activities. The result of the Catur Insan Scholar University (UCIC) International PkM activity is an increase in mobility and ability to move for individuals who receive mobility aids. This can have a positive impact on daily life, allowing them to be more independent and involved in social and economic activities.